Pengaruh Kualitas Layanan Mobile Banking Terhadap Kepuasan Konsumen pada PT. Bank Mandiri (Persero), Tbk. KCP Bandung Cimindi - Putra, Adriansyah Eka; Fauziah, Suci (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
This study aims to evaluate the quality of mobile banking services at PT. Bank Mandiri (Persero), Tbk. KCP Bandung Cimindi, assess consumer satisfaction with these services, and examine the impact of service quality on customer satisfaction at PT. Bank Mandiri (Persero), Tbk. KCP Bandung Cimindi. The research employs a quantitative method with an associative approach. The sampling method used is probability sampling, with a sample size of 100 respondents. Data analysis involves classic assumption tests and hypothesis testing, including simple linear regression analysis, t-tests (partial tests), and the coefficient of determination (R²). The t-test results indicate that the quality of mobile banking services significantly affects customer satisfaction at PT. Bank Mandiri (Persero), Tbk. KCP Bandung Cimindi. This is evidenced by a t-value of 15.177, which is greater than the t-table value of 0.195, with a significance level of 0.000, which is less than 0.05. The coefficient of determination results show that the quality of mobile banking services accounts for 70.22% of the variance in customer satisfaction, while the remaining 29.78% is influenced by other unexamined factors. The service quality dimensions that need improvement are responsiveness and empathy.